THE IMPACT OF INTERNATIONAL TRADE ON REGIONAL ECONOMIC GROWTH CASE STUDY: SOUTH SULAWESI PROVINCE - Pratiwi Musa, Kartika Septiary (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2025)
This study aims to analyze the impact of international trade on economic growth in South Sulawesi Province. In the context of increasing globalization, international trade has become a crucial pillar in driving local economic growth. Using time series data from 2006 to 2023, the analysis was conducted using a Vector Error Correction Model (VECM) approach to understand the relationship between trade activity and Gross Domestic Product (GDP) growth, as well as its impact on employment and community income. The results show a significant positive relationship between trade volume and economic growth, with sectors involved in international trade experiencing faster growth than other sectors. Furthermore, this study found that good infrastructure and supportive government policies play a significant role in maximizing the benefits of international trade. However, challenges such as commodity price volatility and the impact of the COVID-19 pandemic also need to be addressed. These findings provide recommendations for economic policies to increase the contribution of international trade to regional economic development.